Kesahan dan kebolehpercayaan instrumen skala belas kasihan kendiri (SBKK) versi bahasa Melayu - Nor Azzatunnisak Mohd Khatib; Ab Rahman Roseliza-Murni; Suzana Mohd Hoesni; Jamiah Manap (Penerbit Universiti Kebangsaan Malaysia, 2018)
Self-Compassion Scale (SCS) has been used widely throughout the world as an instrument to measure the self-compassionate concept among adolescents and adults. However, within the context of Malaysia this instrument is relatively new and published work on this construct is limited. This study was therefore conducted to measure the psychometric properties of the SCS - Bahasa Melayu version. SCS was a self-report instrument that consisted of 6 subfactors and it was rated on a 5-point Likert scale. Subjects of this study were randomly selected adolescents (n=125) aged 16 years old who resided in Wilayah Persekutuan Kuala Lumpur. The SCS was translated using back translation technique and its validity was determined by face and content validity. Descriptive analysis was used to assess demographic data, while inferential analysis was adopted to check for internal consistency using Cronbach alpha. Results of validity tests revealed that the content of 12 items of the SCS needed to be rephrased. Results of internal consistency analysis demonstrated good reliability values, with Cronbach alpha for total scale α=.80, while the Cronbach alpha values for the sub-scales ranged from α=.60 to α=.70. All in all, these Cronbach alpha values indicated that the SCS was suitable to measure self-compassion construct among Malaysian population. In order to have a deeper understanding of the self-compassion construct and the suitability of SCS for local use, further analyses using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) may need to be conducted.